1989
DOI: 10.1007/bf02381310
|View full text |Cite
|
Sign up to set email alerts
|

A report of behavioral lateralization in an infant orang-utan (Pongo pygmaeus)

Abstract: ABSTRACT. The limb used to perform seven common activities was recorded during weekly observations of an infant orang-utan. For five of these behaviors, preferences were found that remained consistent in their direction, although there were week to week fluctuations in magnitude. Most notably, a right hand preference was found for nonfood reaching and a right hindlimb preference appeared for initiating locomotion. Although initially, food reaching was predominantly with the right hand, a shift toward preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
(12 reference statements)
2
19
0
Order By: Relevance
“…Such a tendency is consistent with the right upper limb preference reported for the initiation of quadruped walking in the four species of great apes [Cunningham et al, 1989;Heestand, 1986;Hopkins & de Waal, 1995] and in humans [Day & MacNeilage, 1996;Seltzer et al, 1990]. As some of the above-cited authors suggested, this could be a common trait in the great apes and humans that would suggest a left hemisphere specialization in the control of locomotion.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Such a tendency is consistent with the right upper limb preference reported for the initiation of quadruped walking in the four species of great apes [Cunningham et al, 1989;Heestand, 1986;Hopkins & de Waal, 1995] and in humans [Day & MacNeilage, 1996;Seltzer et al, 1990]. As some of the above-cited authors suggested, this could be a common trait in the great apes and humans that would suggest a left hemisphere specialization in the control of locomotion.…”
Section: Discussionsupporting
confidence: 78%
“…Walking, ascending, descending, and brachiating were the behavioral categories considered for locomotion, and sitting, lying, hanging, and changing postures were the ones associated with postural control. Whereas right-hand preferences in great apes and humans were previously reported for quadrupedal locomotion on a horizontal surface [Cunningham et al, 1989;Day & MacNeilage, 1996;Forsythe & Ward, 1987;Heestand, 1986;Hopkins & de Waal, 1995;Seltzer et al, 1990], one would expect preferences to emerge in more individuals in the case of climbing or walking on an incline (ascending and descending), as in other restrictive behaviors, since they involve starting from a more unstable position, which requires more balance and support control. Because going over an obstacle, descending to a lower level, and simply walking horizontally may require very different forms of muscular coordination, as they do in humans [Carpenter et al, 1998], the direction of the asymmetry in ascending and descending would not necessarily be the same as in walking.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The results in nearly every study reveal equal numbers of subjects that were left-handed, right-handed, and without a preference (Christel, 1994;Hopkins, 1993;Hopkins, 1995b;Marchant, 1983;Steiner, 1990;Tonooka & Matsuzawa, 1995). This same finding has been reported in other great-ape species, including gorillas (Annett & Annett, 1991;Olson, Ellis, & Nadler, 1990), orangutans (Cunningham, Forsythe, & Ward, 1989;Hopkins, 1993), and bonobos (Hopkins, Bennett, Bales, Lee, & Ward, 1993;Hopkins & de Waal, 1995).…”
supporting
confidence: 67%
“…For example, humans, particularly women, show universal left-sided biases in cradling infants (Damerose and Vauclair, 2002). Researchers have reported a similar left-sided maternal cradling bias in great apes, notably in chimpanzees and gorillas, but not in other primates (Cunningham et al, 1989;Damerose and Vauclair, 2002;Dienske et al, 1995;Fischer et al, 1982;Hopkins, 2004;Lockard, 1984;Manning and Chamberlain, 1990;Manning et al, 1994;Rogers and Kaplan, 1995; Toback, 1999). Evidence of asymmetries in other early mother-infant behaviors of primates, such as nipple preferences, is less clear.…”
mentioning
confidence: 99%